Dakwah Versi Harun Nasution - Alkhendra Alkhendra (Universitas Islam Negeri Imam Bonjol Padang, 2004)
Dakwah is a duty of every Moslem. There are many ways to do this duty, like rhetoric presentations, groups working at society, political activities, using mass media, and so on. All of the t,ways are done to reach the goal of Islamic way of life.This article tries to explain the deconstruction and reconstruction of understanding Islam by Harun Nasution, as a kind of dakwah activity.